Susceptibility of Cell Populations to Transduction by Retroviral Vectors - Wotherspoon, Simon (American Society for Microbiology, 2004)
Retroviral transduction efficiency is related to the multiplicity of infection and the physiological state of the target cells. It is generally not known what proportion of a cell population is susceptible to transduction. We used coinfection with two retroviral vectors containing the marker genes for green fluorescent protein and the truncated human nerve growth factor receptor. In the CD34(+) cell line TF-1 or human primary CD34(+) hematopoietic progenitor cells, it was found that cells transduced with one vector had a better than random chance of transduction by the other vector. A probability model was developed to estimate target cell susceptibility; susceptibility was calculated as the product of the proportions of transgene-positive cells divided by the proportion of double-positive cells. By using this relationship, it was found that susceptibility was related to the target cell type and culture conditions but not the retroviral titer or the retroviral packaging envelope protein used in this study. Cotransduction with two vectors is a relatively simple procedure that provides a means to assess the maximum transduction level possible in a given cell population.